2003
DOI: 10.1046/j.1365-8711.2003.06933.x
|View full text |Cite
|
Sign up to set email alerts
|

On the formation of star clusters in the merger NGC 6240

Abstract: We identified star clusters in archived HST/WFPC2 images of the merger and ultra-luminous infrared galaxy NGC 6240, with the aim of investigating whether star cluster properties (luminosity, age and mass) in such an extreme environment differ from those of clusters in less luminous starburst galaxies. We found 54 star clusters in all of the F450W, F547M and F814W exposures, of which 41 are located in the main body of NGC 6240 and 13 in the galactic tails. Given that only two colours are available to derive two… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(44 citation statements)
references
References 78 publications
(119 reference statements)
3
41
0
Order By: Relevance
“…The immediate implication of a similar result for the NGC 6745 clusters would be that galaxy interactions indeed produce extremely massive star clusters, as also suggested by Maraston et al (2004) based on their analysis of NGC 7252-W3; see also Pasquali, de Grijs & Gallagher (2003) and Pollack, Max & Schneider (2007) for tentative indications that the more massive clusters in the galaxy merger NGC 6240 tend to form closer to the most intense interaction regions near the galaxy's double nucleus. This gives important insights into the still largely unknown star and star cluster formation processes in extreme environments.…”
Section: A "Super" Star Cluster Grown Old?supporting
confidence: 55%
“…The immediate implication of a similar result for the NGC 6745 clusters would be that galaxy interactions indeed produce extremely massive star clusters, as also suggested by Maraston et al (2004) based on their analysis of NGC 7252-W3; see also Pasquali, de Grijs & Gallagher (2003) and Pollack, Max & Schneider (2007) for tentative indications that the more massive clusters in the galaxy merger NGC 6240 tend to form closer to the most intense interaction regions near the galaxy's double nucleus. This gives important insights into the still largely unknown star and star cluster formation processes in extreme environments.…”
Section: A "Super" Star Cluster Grown Old?supporting
confidence: 55%
“…To systematically estimate ages and extinctions for the clumps in Table 2, we used a χ 2 minimization calculation (e.g., Pasquali et al 2003) to determine the fit of the observed colors to that of the models: In this equation, N is the number of colors used in the analysis, obs i is the observed color, model i is the corresponding model color, and σ i is the uncertainty in the obs i color. A good fit is indicated by χ 2 < N. In these calculations, we did not include filters with non-detections.…”
Section: Agesmentioning
confidence: 99%
“…This may thus be an example of an SSC that does not remain bound over the lifetime of the interaction. Nevertheless, a number of SSCs in a variety of galaxies have properties that are promising examples of newly emerging galaxies and globular clusters (see Bastian et al 2005;Lisenfeld et al 2004;Braine et al 2001;Pasquali et al 2003;Gilbert et al 2000).…”
Section: Tidal Tail Stellar Cluster Massmentioning
confidence: 99%